Interculturality in the classroom through animated films - Sevillano García, Sergio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Interculturality is a key concept in the current context when conceiving an educational model. The different cultures, as well as the different societies that exist today, offer endless possibilities and realities that enrich the human experience. Knowing different cultures develops our thinking and prepares us to face situations from a different perspective. That is why, having clear the importance of interculturality, in this study we are going to raise an educational proposal, in which the final objective will be to develop an educational method, a proposal for application in the classroom, located within the first educational cycle (primary).